Incomplete pattern of steroidogenic protein expression in functioning adrenocortical carcinomas - Pereira, SS (2020)
Autonomous steroid secretion is a common feature of adrenocortical carcinomas (ACC), although not always clinically evident owing to inefficient steroidogenesis with increased release of steroid precursors. Our study aim was to analyze the expression profile of four key proteins involved in the steroidogenesis cascade, in different adrenocortical tumors. Expression of proteins involved in steroidogenesis, namely steroidogenic acute regulatory protein (StAR), 11ß-hydroxylase (CYP11B1), aldosterone synthase (CYP11B2) and 17a-hydroxylase (CYP17A1), were analyzed by immunohistochemistry in ACC (n = 14), adenomas presenting with Cushing's syndrome (ACAc) (n = 11) and clinically non-functioning adenomas (ACAn) (n = 15). A percentage of the stained area for each protein was analyzed using ImageJ software for computerized morphometric quantification. CYP11B1, StAR and CYP17A1 expression were significantly lower in ACC when compared to ACAc. In addition, ACC presented co-staining cells for CYP11B1 and CYP11B2. CYP11B1 was the steroidogenic enzyme with the most discriminative power to distinguish ACC from ACAc, with a sensitivity of 100%, specificity of 92%, and an expression higher than 4.44%, indicating the presence of a cortisol secreting adenoma. ACC depicts an incomplete pattern of steroidogenic protein expression, with decreased CYP11B1 and CYP17A1, which could explain the predominant secretion of steroid precursors.